Indonesia and The Criminalization of Illegal, Unregulated, and Unreported Fishing in The Global Level - Ardhani, Irfan (Jurnal Hubungan Internasional, 2021)
The staunch measures taken by President Joko Widodo’s administration in combating Illegal, Unreported, and Unregulated (IUU) Fishing has attracted considerable attention from academia. However, previous studies focused on analyzing law enforcement measures in terms of the sinking-vessel policy. Consequently, they failed to adequately comprehend how Indonesia deals with the problem by criminalizing IUU Fishing at the global level. This article attempts to fill such a gap. Employing the five stages of the historical evolution of a global prohibition regime, introduced by Andreas and Nadelmann (2006), this research investigated the progress of Indonesia’s campaign to criminalize IUU Fishing at the global level and identified some hurdles that Indonesia has to address in fostering the advancement of the criminalization campaign. This article discovered that Indonesia has arrived at the third stage of making the global prohibition regime of TOC in the fisheries industry and has to deal with the hurdles of argumentation weakness and disagreement from several countries